2021
DOI: 10.1155/2021/6634309
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Complementary and Alternative Medicine in the Treatment of Female Infertility

Abstract: Female infertility is a state of fertility disorder caused by multiple reasons. The incidence of infertility for females has significantly increased due to various factors such as social pressure, late marriage, and late childbirth, and its harm includes heavy economic burden, psychological shadow, and even marriage failure. Conventional solutions, such as hormone therapy, in vitro fertilization (IVF), and embryo transfer, have the limitations of unsatisfied obstetric outcomes and serious adverse events. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 91 publications
0
20
0
1
Order By: Relevance
“…There are several reports, including systematic reviews, on the effects of traditional Chinese medicine (TCM) for infertile women (9)(10)(11)(12)(13). Most of these demonstrated the effectiveness and safety of TCM, although a small number of trials did not show effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports, including systematic reviews, on the effects of traditional Chinese medicine (TCM) for infertile women (9)(10)(11)(12)(13). Most of these demonstrated the effectiveness and safety of TCM, although a small number of trials did not show effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 2, traditional herbal medicines have been used to treat female infertility [191]. Several reports have suggested that traditional herbal formulas and medicinal herbs successfully improve endometrial receptivity and might be an alternative option for improving the outcome of embryo implantation [192][193][194].…”
Section: Possible Role Of Autophagy On the Effect Of Medicinal Herbal Drugs As Embryo Implantation Enhancermentioning
confidence: 99%
“…CAM includes many products and medical practices that are not conventional therapies in western countries, including not only traditional medicines and folk therapies, but also many new therapies that cannot be covered by medical insurance, such as traditional Chinese medicine (TCM; including Chinese herbal medicine, acupuncture, qigong, etc. ), Indian medicine, medicinal food, health food, aromatherapy, vitamin therapy, dietary therapy, psychotherapy, spa therapy, and oxygen therapy [ 19 , 20 ]. CAM is favored by many countries and nationalities because of its natural ingredients and methods, its convenience, and its low costs.…”
Section: Introductionmentioning
confidence: 99%